Evaluation of the Impacts of Foreign Remittances on Socio-Economic Conditions of Recipients Household in District Chitral - Hasina Wajid; Sami Ullah; M. Yoserizal Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The study was undertaken in district Chitral to examine the socio-economic impacts of foreign remittances on recipients household. Primary data was collected through well-structured questionnaire from 60 randomly selected respondents. Both descriptive and inferential statistics were undertaken for the analysis of data. The result concluded a positive significant impact of foreign remittances on recipient household education expenditure, recipient household health expenditure and recipient household income. It was noted that immigrants were migrated due to their poor economic condition. It was also observed that due to lack of education and training, 70% of immigrants were doing labor and were earning less.